The ompU Paralogue vca1008 Is Required for Virulence of Vibrio cholerae - Osorio, Carlos G. (American Society for Microbiology, 2004)
We made single and combined mutations in ompU, ompT, and the two putative porin genes vca1008 and vc0972. The fitness of the strains was tested in vitro and in the infant mouse model of intestinal infection. We also studied the transcriptional induction of vca1008 in vitro and during mouse infection. We show that vca1008 is induced during infection and is necessary and sufficient (in the absence of ompU, ompT, and vc0972) for infection.